2013
DOI: 10.5152/akd.2013.188
|View full text |Cite
|
Sign up to set email alerts
|

Relation of neutrophil -to- lymphocyte ratio with the presence and complexity of coronary artery disease: an observational study

Abstract: Objective: The neutrophil -to-lymphocyte ratio (NLR) is a new predictor for cardiovascular risk and mortality. The SYNTAX score is an angiographic tool used in grading the complexity of coronary artery disease (CAD). However, its relation with CAD severity and complexity is not yet known. We hypothesized that NLR would be associated with a greater complexity of CAD as assessed using the SYNTAX score. Methods: This cross-sectional observational study included 106 patients who had undergone coronary angiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 23 publications
6
88
1
4
Order By: Relevance
“…During the pathogenesis of cardiac disease and arrhythmia, there is an increase in inflammatory activity [23][24][25] and in SCF patients inflammatory activity is further increased [6,26]. In our study, the inflammation level was evaluated by NLR and our results correlated with previous studies demonstrating that inflammation levels were higher in SCF patients compared to controls.…”
Section: Discussionsupporting
confidence: 81%
“…During the pathogenesis of cardiac disease and arrhythmia, there is an increase in inflammatory activity [23][24][25] and in SCF patients inflammatory activity is further increased [6,26]. In our study, the inflammation level was evaluated by NLR and our results correlated with previous studies demonstrating that inflammation levels were higher in SCF patients compared to controls.…”
Section: Discussionsupporting
confidence: 81%
“…There was also statistically significant association between the groups (p <0.001). 5,21,22,23 In this study, we found a relation of ESR, NLR with the presence of coronary artery disease. There is no doubt in cardiovascular medical science that atherosclerosis is a chronic inflammatory disease.…”
Section: Discussionmentioning
confidence: 56%
“…Sonmez O et al, (2013) also found higher total count WBC in patients with coronary artery disease (p <0.001). 5 In our study mean NLR in Group I was 2.76 (±0.74), whereas it was 1.56 (±0.15) in Group II. There was statistically significant association between two groups in this regards (p <0.001).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…1 NLR is a new indicator for cardiovascular risk and mortality and by which we can predict the risk of coronary artery disease (CAD) in type 2 DM patients. 2 Increased NLR is associated with major adverse cardiac events in type 2 diabetes mellitus patients. 3,4 The relationship between various inflammatory markers and CAD has been established.…”
Section: Introductionmentioning
confidence: 99%